Oral Health and Nutrition in Older People - Angus W. G. Walls, BDS, PhD, FDSRCS; Jimmy G. Steele, BDS, PhD, FDSRCPS; Aubrey Sheiham, BDS, (Blackwell Synergy, 2000)
The theoretical link between foods choice and masticatory efficiency has long been established. Recent evidence has confirmed this association, demonstrating a progressive alteration in food choice with decreasing numbers of teeth, with the greatest effect being among those who are edentulous. This altered food selection results in significant differences in the hematological status for some key nutrients in the one study in which this association was investigated. This paper summarizes some of the literature relevant to diet as a risk factor for systemic disease and identifies areas where alfered food choice as a consequence of reduced masticatory efficiency might be placing individuals at increased risk of life-threatening conditions, such as atherosclerosis and cancer.